Decoding signs of identity : Egyptian workmen's marks in archaeological, historical, comparative and theoretical perspective - Haring, B. J. J.; Van der Moezel, K. V. J.; Soliman, D. M. (Egyptologische uitgaven, 2018)
Decoding Signs of Identity' is the volume of proceedings resulting from the symposium with the same name and held in Leiden, 13-15 December 2013, in the framework of the NWO research project ?Symbolizing Identity: Identity marks and their relation to writing in New Kingdom Egypt?. The aim of the project, and indeed of the symposium, was to investigate identity marks of Ancient Egyptian workmen, both in a specialist, in-depth manner, and in a more general, comparative perspective. The reader will recognise both of these approaches in the present collection of papers. In the course of its three sections, the topic is narrowed down from general considerations and non-Egyptian cases, to various sorts of Ancient Egyptian identity marks, and finally to the specific marking system of the royal necropolis workforce of the Egyptian New Kingdom, which was the core material of the NWO project. This volume can be considered a follow-up to 'Pictograms or Pseudo Script?' (EU XXV, 2009), and testifies to the continuing scholarly interest in systems of identity marks, both in Egyptology and outside.